English private law. - Burrows, A. S. (Andrew S.) (Oxford : Oxford University Press, 2013)
This work has become a key point of reference on English private law for lawyers in the UK and throughout the world. Readers will find a lucid, concise, and authoritative overview of all the key areas of private law. Each section is written by an acknowledged expert, who provides a clear distillation and analysis of the subject. The 3rd edition includes all the recent developments since the publication of the 2nd edition in 2007.
Previous edition: 2007.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on September 4, 2013).
Keywords: Civil law -- England; Civil law -- Wales